O5-S4.03 HIV testing among patients infected with Neisseria gonorrhoeae-STD surveillance network, USA, 2009–2010. (10th July 2011) - Bradley, H; Asbel, L; Bernstein, K; Mattson, M; Pathela, P; Pino, R; Samuel, M; Schwebke, J; Stenger, M; Tabidze, I; Zenilman, J; Dowell, D; et al.
Abstract : Background: An estimated 21% of 1.1 million HIV-infected US residents do not know they are infected and may unknowingly transmit HIV. Because people with sexually transmitted diseases (STDs) are at increased risk of HIV, CDC recommends HIV screening for patients seeking STD treatment. We investigated whether patients given a diagnosis of Neisseria gonorrhoeae during January 2009-June 2010 were concurrently tested for HIV. Methods: We used data from interviews with randomly selected gonorrhoea-infected patients in the 12 state and local health jurisdictions constituting the STD Surveillance Network. We compared the prevalence of HIV testing concurrent with gonorrhoea testing or treatment among patients seeking care in STD clinics and patients in other practice settings (emergency rooms, public and private outpatient facilities, hospitals, and family planning clinics). Results: Of 6658 eligible patients, 3462 (52%) were successfully interviewed. Complete data were available for 1845/3462 (53%). Of these, 51% were tested for HIV when they were tested or treated for gonorrhoea. The proportion of gonorrhoea patients tested for HIV ranged from 22% to 74% by jurisdiction. STD clinic patients were more likely to be tested for HIV than those in other practice settings (61% vs 46%, p <0.01), see Abstract O5-S4.03 figure 1 and women were more likely than men to be tested for HIV in STD clinics (71% vs 58%, p=0.01). HIV testing was more common among black (53%) and Hispanic women (54%) compared with white women (36%, p=0.01). Men who have sex with men (MSM) were generally more likely to be tested for HIV compared with other men (56% vs 48%, p=0.02), though 58% of both MSM and MSW were tested for HIV in STD clinics. We found no association between HIV testing and race (among men), age, or having multiple sex partners. Conclusions: HIV testing among gonorrhoea-infected patients is sub-optimal. While patients are more likely to be HIV-tested in STD clinics than in other practice settings, even STD clinics miss many opportunities to test high risk groups such as MSM, who are less likely than women to be HIV tested in this setting. Interventions are urgently needed to increase HIV testing among STD patients.